Does a vegetable-first, optimal default strategy improve children's vegetable intake? A restaurant-based study. (June 2019) - Ferrante, Mackenzie J.; Johnson, Susan L.; Miller, Jeffrey; Moding, Kameron J.; Bellows, Laura L.
Highlights: Use of a vegetable appetizer as an optimal default increased children's vegetable intake. Vegetable appetizers may reduce competition among vegetables and energy-dense restaurant foods. Results show the ability of behavioral economic strategies to improve intake of healthful food.